2021
DOI: 10.1186/s12967-021-02809-2
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effect of IL-12 gene-modified bone marrow mesenchymal stem cells combined with Fuzheng Yiliu decoction in an in vivo glioma nude mouse model

Abstract: Background Glioma is a complex cancer with a high morbidity and high mortality. Bone marrow mesenchymal stem cells (BMSCs) have shown promise as an excellent cell/drug delivery vehicle for gene-targeted therapy; however, maintaining genetic stability and biological activity remains difficult. Furthermore, whether BMSCs support or inhibit tumor growth remains debated. This study investigated whether a traditional Chinese medicine fomular, Fuzheng Yiliu decoction (FYD) had a synergistic antitumor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Meanwhile, glioma U251 cell-bearing BALB/c nude mice experienced robust decreases in tumor volume upon treatment with FYD plus MSC-IL-12. Moreover, a combine treatment of FYD and MSC-IL-12 induced higher Bax and lower Bcl-2 expression and also supported higher serum IL-12 and INF-γ levels compared with monotherapy with FYD or MSC-IL-12 (67). Besides, intramural injection of genetically modified MSCs co-expressing IL-12 and IL-7 caused a marked inversion of the CD4+/CD8+ T-cell ratio with an intricate antitumor response mainly mediated by CD8+ effector T cells in glioma tumor-bearing mice (68).…”
Section: Mscs As a Carrier For Ilsmentioning
confidence: 69%
See 1 more Smart Citation
“…Meanwhile, glioma U251 cell-bearing BALB/c nude mice experienced robust decreases in tumor volume upon treatment with FYD plus MSC-IL-12. Moreover, a combine treatment of FYD and MSC-IL-12 induced higher Bax and lower Bcl-2 expression and also supported higher serum IL-12 and INF-γ levels compared with monotherapy with FYD or MSC-IL-12 (67). Besides, intramural injection of genetically modified MSCs co-expressing IL-12 and IL-7 caused a marked inversion of the CD4+/CD8+ T-cell ratio with an intricate antitumor response mainly mediated by CD8+ effector T cells in glioma tumor-bearing mice (68).…”
Section: Mscs As a Carrier For Ilsmentioning
confidence: 69%
“…In another study, injection of MSC-IL-12 into Ast11.9-2 glioma cell-bearing C57/B16 mice caused enhanced NK cell infiltration in brain tissue, and thereby exerted an improvement in non-specific cell lysis, while could not induce significant promotion in overall survival rates of the treated mice compared with control mice (66). Nonetheless, it was demonstrated that treatment with Fuzheng Yiliu decoction (FYD), a traditional Chinese medicine, in combination with MSC-IL-12 therapy could elicit synergistic antitumor effects in glioma-bearing nude mice (67). Meanwhile, glioma U251 cell-bearing BALB/c nude mice experienced robust decreases in tumor volume upon treatment with FYD plus MSC-IL-12.…”
Section: Mscs As a Carrier For Ilsmentioning
confidence: 99%
“…Human glioma U251 cell culture U251 cells were cultured as described previously [21] at saturated humidity in Roswell Park Memorial Institute (RPMI) 1640 medium, which was changed every 2-3 days.…”
Section: Page 4/16mentioning
confidence: 99%
“…The mouse feed was not supplemented with foetal bovine serum in this study. Mice were handled post mortem as described previously [21]. The cell surface molecular markers CD44, CD105, CD34, CD45, and CD11b were detected by ow cytometry [5,22,23].…”
Section: Primary Culture Isolation and Identi Cation Of Bmscsmentioning
confidence: 99%
See 1 more Smart Citation